2023
DOI: 10.1021/jacs.2c09274
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Aldehydes into Carboxylic Acids by a Mononuclear Manganese(III) Iodosylbenzene Complex through Electrophilic C–H Bond Activation

Abstract: The oxidation of aldehyde is one of the fundamental reactions in the biological system. Various synthetic procedures and catalysts have been developed to convert aldehydes into corresponding carboxylic acids efficiently under ambient conditions. In this work, we report the oxidation of aldehydes by a mononuclear manganese(III) iodosylbenzene complex, [MnIII(TBDAP)(OIPh)(OH)]2+ (1), with kinetic and mechanistic studies in detail. The reaction of 1 with aldehydes resulted in the formation of corresponding carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 93 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…At the fundamental level, it is revealed that the hydride transfer is composed of H atom abstraction, followed by a fast electron transfer. 54,55 Cu-Mn mixed metal oxide is the concordant pair reported for the oxidation of p-cresol and toluene. 56,57 The selective oxidation of benzyl alcohol to benzaldehyde has been investigated using molecular oxygen over copper-manganese mixed oxide, which showed improved catalytic activity and product selectivity.…”
Section: Introductionmentioning
confidence: 63%
“…At the fundamental level, it is revealed that the hydride transfer is composed of H atom abstraction, followed by a fast electron transfer. 54,55 Cu-Mn mixed metal oxide is the concordant pair reported for the oxidation of p-cresol and toluene. 56,57 The selective oxidation of benzyl alcohol to benzaldehyde has been investigated using molecular oxygen over copper-manganese mixed oxide, which showed improved catalytic activity and product selectivity.…”
Section: Introductionmentioning
confidence: 63%
“…Synthesis of aryl and alkyl carboxylic acids via oxidation of the corresponding aldehydes under mild conditions using manganese catalysis was recently reported by the Cho group (Scheme 13). 47 This provides an alternate approach to the Pinnick oxidation for carboxylic acid synthesis. Mechanistic studies revealed the reaction to proceed via a net hydride transfer from the aldehyde to the catalyst, forming an intermediate oxonium species which reacts further to form the carboxylic acid.…”
Section: Mn Catalysismentioning
confidence: 99%
“…After we reported the first example of a mononuclear nonheme manganese(III)−iodosylbenzene complex, we found that 9 is reactive with aldehydes, affording corresponding carboxylic acids. 52 The addition of cyclohexanecarboxaldehyde (CCA) to the solution of 9 resulted in the decay of 9 to [Mn III (TBDAP)-(OH)(A)] n+ (A = OTf − or CH 3 CN) and the formation of cyclohexanecarboxylic acid (66%) as a product. A Hammett plot obtained from the oxidation of benzaldehyde derivatives afforded a negative slope of −1.9, indicating an electrophilic pathway.…”
Section: Catalytic Oxidation Of Aldehyde To Carboxylic Acid By a Mang...mentioning
confidence: 99%